The Development of Math Learning Tools for Elementary Based on 2013 Curriculum in Coastal Area - Zuhri D, Zuhri D; Maimunah, Maimunah; Yuanita, Putri (Journal of Educational Sciences, 2020)
K13 has not been implemented optimally, one of them is caused by the inability to develop learning tools that apply the scientific approach. Student-environment contexts rich in learning resources can not be utilized by teachers. This condition encourages us to conduct a study in developing K13-based elementary school educational devices by utilizing coastal area contexts. Learning tools developed are lesson plans, learning media and teaching materials. The purpose of this study is to produce lesson plans, learning media and teaching materials that are scientifically designed coastal areas are valid so feasible to use. In the development of these learning tools, the researcher uses a4-D framework model. The research data was collected using a validated questionnaire. Validation results indicate that: (1) the validity test of lesson plans are in a very valid category; (2) validity test of valid category media; and (3) the validity test of the teaching materials is in a very valid category.